Role Of Generational Age Owners Of Smes In Development Of Marketing Agility - Tiyan Fatkhurrokhman; Weni Novandari; Refius Pradipta Setyanto (International Journal of Business and Quality Research, 2024)
The importance of marketing agility in facing rapidly changing market dynamics has become a major concern in modern marketing literature. Marketing agility, defined as an organization’s ability to respond quickly and efficiently to market changes, is considered a key success factor in complex and uncertain business environments. Small and medium-sized enterprises (SMEs) play a vital role in the national and global economy, but often face significant challenges in adopting marketing agility. This study aims to identify and analyze the influence of the age of SME owners on marketing agility. The main focus is to determine whether Generation Y SME owners exhibit higher levels of marketing agility compared to Generation X owners, as well as to evaluate marketing agility levels across various age groups of SMEs. The method used is an independent sample t-test, with data obtained through questionnaires administered to Generation X (born 1980-1990) and Generation Y (born 2000-2018) SME owners in the Kebumen Regency. The research findings indicate a significant difference in the ability to develop marketing agility between the two generational age groups. Generation Y SME owners demonstrate better abilities, with an average score of 85.5455, compared to Generation X, which has an average score of 68.1463. In conclusion, Generation Y SME owners exhibit higher levels of marketing agility than Generation X. These findings provide critical insights for designing more effective interventions to support the sustainability and growth of SMEs in the digital era.